Emerging Roles of Eosinophils and Eosinophil-Derived Lipid Mediators in the Resolution of Inflammation - Isobe, Yosuke; Kato, Taiga; Arita, Makoto (Frontiers in Immunology, 2012)
Acute inflammation and its resolution are essential processes for tissue protection and homeostasis. Once thought to be a passive process, the resolution of inflammation is now shown to involve active biochemical programs that enable inflamed tissues to return to homeostasis. The mechanisms by which acute inflammation is resolved are of interest, and research in recent years has uncovered new endogenous anti-inflammatory and pro-resolving lipid mediators (i.e. lipoxins, resolvins, protectin, and maresin) generated from polyunsaturated fatty acids (PUFAs). This review presents new insights into the cellular and molecular mechanisms of inflammatory resolution, especially the roles of eosinophils, and a series of omega-3 PUFA derived anti-inflammatory lipid mediators that they generate.